Analyzing Process Capability Indices (PCI) and Cost of Poor Quality (COPQ) to Improve Performance of Supply Chain - Asep Ridwan; Bernd Noche (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
Many ports have inefficient and ineffective activities in the entire of Supply Chain. Many methods and tools are used to analyze performance of Supply Chain. This study based on our practical experience in implementation of Six Sigma Methodology in port. The main purpose of our research is to analyze Process Capability Indices (PCI) and Cost of Poor Quality (COPQ) for improving performance of Supply Chain in port. PCI and COPQ is performance indicator of Six Sigma Methodology as one of Quality Improvement Method. Case study has been taken in CDG Port, Indonesia. Three big cargos handling have been selected to be analyzed PCI and COPQ, as follow: fertilizer, slab steels, and iron ore. Data were collected by direct observation and interview with Logistics Service Department of CDG Port. The result of Process Capability Indices in handling of cargo is 0.06 in average. This result shows that process capability in cargo handlings have not capable to meet the customer requirements. Meanwhile, Cost of Poor Quality in cargos handling is about 700,449 USD in average and 39.02 % from the sales in average. This cost is still high if it is compared with the sales. Many potential improvements to increase process capability and decrease cost of poor quality. With Six Sigma Methodology, Process Capability Indices and Cost of Poor Quality can be analyzed for improving performance of Supply Chain in port.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; capability process indices; cost of poor quality; six sigma; port